Stratification of eosinophilic asthma patients treated with reslizumab and GINA Step 4 or 5 therapy. Issue 3 (17th August 2017) - Brusselle, Guy; Canvin, Janice; Weiss, Sivan; Sun, Shawn X.; Buhl, Roland
Reslizumab, an anti-interleukin-5 monoclonal antibody, significantly reduces exacerbation frequency and improves lung function, asthma control and quality of life in adults with severe eosinophilic asthma, as demonstrated in Phase III studies. This secondary analysis assessed reslizumab's efficacy in patients receiving baseline treatment per Global Initiative for Asthma (GINA) Step 4 and Step 5 guidelines. Pooled data from duplicate, Phase III, reslizumab versus placebo studies in patients with severe eosinophilic asthma (blood eosinophils ≥400 cells·µL −1 ) were stratified by baseline therapy. Efficacy assessments were exacerbation rates and changes from baseline forced expiratory volume in 1 s (FEV1 ) and patient-reported outcomes. Of 953 patients, 69% (n=657) and 11% (n=106) were receiving Step 4 and Step 5 therapy, respectively. Compared with placebo, reslizumab reduced exacerbation rates by 53% (95% CI 0.36–0.62) and 72% (95% CI 0.15–0.52), in Step 4 and Step 5 groups respectively. By study end, reslizumab increased FEV1 in Step 4 and Step 5 groups by 103 mL (95% CI 52–154 mL) and 237 mL (95% CI 68–407 mL), respectively. Reslizumab also improved patient-reported outcomes compared with placebo in both groups. Reslizumab reduces exacerbation rates and improves lung function and patient-reported outcomes in patients with eosinophilic asthma receiving therapy per Steps 4 and 5 of the GINA guidelines. Subanalyses of Phase III data: severe eosinophilic asthma patients benefit from reslizumab plus GINA 4/5 therapy http://ow.ly/6zJU30e8T2b